Electric field- and strain-induced bandgap modulation in bilayer C2N - Klichchupong Dabsamut; Tosapol Maluangnont; Pakpoom Reunchan; Jiraroj T‐Thienprasert; Sirichok Jungthawan; Adisak Boonchun (Applied Physics Letters, 2022)
Recently, the C2N monolayer with an optical bandgap of 1.96 eV has emerged as a novel two-dimensional material for modern optoelectronic devices. Herein, we report its bandgap modulation by using a simple bilayer formation that includes the application of an electric field and strain. We identify four energetically favorable bilayer configurations (AA-, AB-, AB′-, and Min-stacking) by using a hybrid functional, obtaining a calculated bandgap of 1.3–1.6 eV. When subjected to a perpendicular electric field up to 4 V/nm, the bandgap decreases by as much as 0.5 eV, which correlates with the increasing energy of the valence-band maximum, where the N-px and N-py states shift closer to the N-pz state. Without the electric field, the bandgap decreases when the interlayer distance is contracted by a compressive strain. We express the strain (or interlayer distance) and the physical applied pressure via the stabilized jellium equation of state. For the Min-stacking configuration, the bandgap decreases from 1.75 to 0.9 eV upon applying a pressure of 35 GPa. The strain-induced reduction in the bandgap is similarly monitored under an applied electric field. Our theoretical work suggests that the electric field and strain (or applied pressure) can be used to tune the electronic properties of the bilayer C2N.
Keywords: Graphene research and applications; 2D Materials and Applications; Boron and Carbon Nanomaterials Research